2018
DOI: 10.1177/0959683618788701
|View full text |Cite
|
Sign up to set email alerts
|

A 2000-year record of ocean influence on Jakobshavn Isbræ calving activity, based on marine sediment cores

Abstract: The Greenland Ice Sheet has experienced significant mass loss in recent years. A substantial component of this is attributable to the retreat of marine-terminating outlet glaciers, which lose mass through increases in calving, submarine melting and terrestrial meltwater discharge. In terms of iceberg production, Jakobshavn Isbræ is the largest marine-terminating glacier in Greenland, yet relatively little is known about its history before the first glacier margin observations in 1851. Two marine sediment cores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 98 publications
1
34
2
Order By: Relevance
“…Whereas the SST record shows a clear change in variability around 1900 CE, the IRD record remains relatively constant in this period. This is in contrast with studies of the larger marine terminating glaciers, for example, Jakobshavn Isbræ (Wangner et al, ) and Helheim Glacier (Andresen et al, ), where increased IRD was related to observed glacier margin retreat and climate warming, suggesting a link between ocean forcing, iceberg production, and glacier retreat.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…Whereas the SST record shows a clear change in variability around 1900 CE, the IRD record remains relatively constant in this period. This is in contrast with studies of the larger marine terminating glaciers, for example, Jakobshavn Isbræ (Wangner et al, ) and Helheim Glacier (Andresen et al, ), where increased IRD was related to observed glacier margin retreat and climate warming, suggesting a link between ocean forcing, iceberg production, and glacier retreat.…”
Section: Discussioncontrasting
confidence: 87%
“…Whereas the SST record shows a clear change in variability around 1900 CE, the IRD record remains relatively constant in this period. This is in contrast with studies of the larger marine terminating glaciers, for example, Jakobshavn Isbrae (Wangner et al, 2018) and Helheim Glacier (Andresen et al,…”
Section: Iceberg Rafting Within Nørre Skjoldungesundcontrasting
confidence: 68%
See 2 more Smart Citations
“…Environmental factors such as sea‐ice conditions (frozen vs. unfrozen fjord) and ambient water temperature can depress or enhance the general ice‐rafting signal and therefore complicate its interpretation as an indicator of calving intensity. In addition, IRD variability has an inherent random component due to local effects such as differential iceberg transport pathways and variations in the sediment load and grain‐size distribution of icebergs (Andrews, ; Wangner et al , ). Our results confirm this high spatial variability since the IRD fluxes vary markedly between core sites with little to no correlation (Fig.…”
Section: Discussionmentioning
confidence: 99%